2013
DOI: 10.1007/s12088-013-0377-0
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Production of Lactic Acid from Sweet Sorghum Juice by a Newly Isolated Lactobacillus salivarius CGMCC 7.75

Abstract: Sweet sorghum juice was a cheap and renewable resource, and also a potential carbon source for the fermentation production of lactic acid (LA) by a lactic acid bacterium. One newly isolated strain Lactobacillus salivarius CGMCC 7.75 showed the ability to produce the highest yield and optical purity of LA from sweet sorghum juice. Studies of feeding different concentrations of sweet sorghum juice and nitrogen source suggested the optimal concentrations of fermentation were 325 ml l -1 and 20 g l -1 , respective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It is important to emphasize that utilization of sweet sorghum turned to the production of other chemical compounds from the carbohydrate content of the raw juice such as lactic acid [34][35][36][37], butanol [38], hydrogen [28,39,40], acetone [41], lipids [42] gained more importance. Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…It is important to emphasize that utilization of sweet sorghum turned to the production of other chemical compounds from the carbohydrate content of the raw juice such as lactic acid [34][35][36][37], butanol [38], hydrogen [28,39,40], acetone [41], lipids [42] gained more importance. Among the platform molecules levulinic acid could play a key role in the chain [43], since it is the raw material of a proposed platform chemical (gamma-valerolactone) that can be obtained by its selective hydrogenation [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Ueno et al studied utilization of grape invertase from grape juice for sucrose hydrolysis, while Hetényi et al performed hydrochloric acid treatment. In contrast, L. delbrueckii and Enterococcus faecalis were able to produce directly LA on sugar beet molasses, while Lui et al reported direct LA production by L. salivarius on sweet sorghum juice.…”
Section: Introductionmentioning
confidence: 94%
“…13 In a previous study, when sucrose was the sole carbon source, the cell biomass accumulation was much lower compared with a medium containing glucose or fructose. 13 Liu et al 35 also found that the consumption rate of sucrose in sweet sorghum juice was significantly slower than that of reducing sugar during the lactic acid production process. These results indicated that sucrose in sweet sorghum juice should be hydrolyzed to reducing sugar before use in the medium as carbon source.…”
Section: Fermentation Of Glucose Fructose and Mixed Sugars (Glucose mentioning
confidence: 99%